Injection Molding Integration of Theory and Modeling Methods - Zheng, Rong.; Tanner, Roger I.; Fan, Xi-Jun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book covers fundamental principles and numerical methods relevant to the modeling of the injection molding process. As injection molding processing is related to rheology, mechanical and chemical engineering, polymer science and computational methods, and is a rapidly growing field, the book provides a multidisciplinary and comprehensive introduction to the subjects required for an understanding of the complex process. It addresses the up-to-date status of fundamental understanding and simulation technologies, without losing sight of still useful classical approaches. The main chapters of the book are devoted to the currently active fields of flow-induced crystallization and orientation evolution of fiber suspensions, respectively, followed by detailed discussion of their effects on mechanical properties, shrinkage and warpage of injection-molded products. The level of the proposed book will be suitable for interested scientists, R&D engineers, application engineers, and graduate students in engineering.
Introduction -- Fundamentals of Rheology -- Modeling of Mold Filling and Post Filling -- Crystallization -- Flow-Induced Alignment in Short-Fiber Reinforced Polymers -- Shrinkage and Warpage -- Mold Cooling -- Computational Techniques.
Keywords: Engineering; Polymers; Chemical engineering; Hydraulic engineering; Structural control (Engineering).; Materials; Engineering; Operating Procedures, Materials Treatment; Industrial Chemistry/Chemical Engineering; Structural Materials; Polymer Sciences; Engineering Fluid Dynamics